Statistical Analysis of Time and Cost Efficiency of Construction Dispute Resolution Through Mediation Compared to Arbitration - Lutfi Mustakim; Sami’an; Sarwono Hardjomuljadi (Journal of Law, Politic and Humanities, 2025)
Non-litigation conflicts can be settled in a number of ways, including through arbitration and mediation. "A method for testing a particular theory by examining the relationship between variables" is the quantitative approach that is employed. The study's findings indicate that the time frames for arbitrating and mediating disputes differ; specifically, the arbitration ruling must be rendered no later than 30 days following the conclusion of the dispute examination. The cost of using the mediation room is not included in the price of using mediation to settle issues in court. This period may be extended, nevertheless, by the arbitration panel or the lone arbitrator. After the mediator is chosen, the mediation procedure can take up to 40 working days, and the arbitration ruling is final and binding on the parties. A maximum extension of 14 working days may be made to this time frame. In the event that mediation produces a written agreement, the parties are required to draft and sign it. The fees for arbitrating disputes differ based on the arbitration organization and the amount of the claim; they could include Registration cost: The registration cost for the arbitration request, Cost of administration: The arbitration administration charge is determined using a tariff scale. Arbitrator's fee: The cost of hiring arbitrators is determined using a tariff scale. along with The cost of hearing: The parties, respondent, or applicant bear the pro rata costs of the arbitration hearing.